The Effect of Return on Assets, and Debt to Equity Ratio on Value of Automotive Sub Sector Companies in Indonesia Stock Exchange - Andy; Gursida, Hari; Sasongko, Hendro (Journal of Social Transformation and Regional Development, 2021)
The purpose of this study is to find out and test the influence of Return On Assets (ROA), and Debt to Equity Ratio (DER) on the value of automotive sub-sector companies on the Indonesia Stock Exchange (IDX) as measured by the Price Book Value (PBV) during 2015-2019. The research was conducted by observing and downloading financial statements and recording summaries in IDX. The research uses verification research with explanatory survey method. Sampling in this study uses purposive sampling method with secondary data in the form of annual report and summary of company performance that has complete financial data during 2015-2019 with a total of 12 companies samples. Data analysis method using data panel regression. The result is that (1) ROA affects the value of the company with a positive coefficient, (2) DER affects the value of the company with a positive coefficient. With these results, the company must adjust the financial ratios and use of debt so that the value of the company continues to increase.